Особливості травматичних пошкоджень у коней в умовах Дніпропетровської області - Білий, Дмитро Дмитрович; Beliy, Dmitry Dmitrievich; Beliy, Dmitry; Beliy, D. D.; Bely, Dmitry Dmitrievich; Bely, Dmitry; Bely, D. D.; Bilyi, D. D.; Bilyi, D.; Belyi, D. D.; Bilyi, Dmytro; Bily, Dmytro; et al. (Дніпропетровський ДАЕУ, 2015)
Проведено аналіз поширеності, особливостей клінічного перебігу травматичних пошкоджень у коней в умовах Дніпропетровської області. Встановлено, що хірургічні захворювання виявляються у 26,53 % від всіх хвороб незаразної етіології; при цьому рани діагностуються у 50,77 %, забої – 26,15 %, розтягнення – 18,46 %, розриви – 4,62 % тварин. Відкриті механічні пошкодження характеризувались змішаним ураженням (колото-різані, рвано-забиті тощо), діагностуючись частіше у тварин, старших 4 років (51,52 %), влітку (54,55 %), не залежно від ділянки тіла. Закриті травми мають аналогічні особливості, за виключення місць розташування – у 90,61 % пацієнтів вони локалізувались на кінцівках. Diseases of horses with traumatic etiology occupy a leading place among surgical pathology, especially if rules of maintenance and feeding do not properly observe. Injuries in sport horse represent one of the major problems of modern veterinary medicine and bring significant economic damage to livestock. Sport horses with increased physical activity, have significantly more limb strikes than animals using for farming. Anti-injury therapy of animals and, above all, with open mechanical damage showed that the main role is given to medical therapy that can significantly reduce economic losses. Given the high prevalence and significant economic losses from locomotor system diseases, the problem of early diagnosis and effective provision of veterinary care at this stage is relevant and requires further deep study. Background injuries in horses caused aim of the study: to determine the features of traumatic injuries in horses in Dnipropetrovsk region. The review included medical history, the general and local changes in the area of pathological focus studied by conventional methods. If necessary, it used special techniques (radiography, ultrasound diagnosis, determination of blood biochemical parameters, etc.). They help to evaluate lesion volume and nonviable tissue, the degree of expression of the inflammatory response and more. Conducted research revealed the following. Among non-contagious pathology in horses in 26.53% of cases are diagnosed surgical diseases, including open injuries recorded in 50.77% of the animals and closed - in 49.23% of patients. Established that traumatic lesions recorded in most cases in adult animals (open / closed - 51.52 / 59.37%) in summer and autumn (were respectively: 54.55 / 46.87 and 18.18 / 31 25%). These closed injuries (90.61%) in horses were found on the extremities; similar features have been detected for wounds. The basis of preventive measures of injuries in horses is make feeding and maintenance optimization, operating conditions, timely diagnosis of animal diseases.
Features traumatic injuries in horses in Dnipropetrovsk region
Білий Дмитро Дмитрович https://orcid.org/0000-0003-3896-0384
Keywords: локалізація; localization; коні; horses; хірургічні хвороби; surgical diseases; травматичні пошкодження; traumatic injuries; поширеність; distribution